Improving the performance of the Ba0.5Sr0.5Co0.8Fe0.2O3-δ cathode for proton-conducting SOFCs by microwave sintering. Issue 16 (November 2019) - Liu, Wenyun; Kou, Hongning; Wang, Xianfen; Bi, Lei; Zhao, X.S.
Abstract: In this study, we prepared a Ba0.5 Sr0.5 Co0.8 Fe0.2 O3- δ (BSCF) cathode layer for proton-conducting solid oxide fuel cells using microwave sintering. Unlike traditional sintering, which is carried out at 1000 °C for a few hours, the microwave sintering method allows the BSCF cathode layer to adhere well with the electrolyte layer after sintering at 900 °C for 10 min. This strategy helps the cathode layer maintain a microstructure favourable for cathode reactions and mitigate the potential diffusion of elements between it and the BaZr0.1 Ce0.7 Y0.2 O3-δ electrolyte, leading to improved cell resistance. The cell with the BSCF cathode layer sintered by the microwave method has a power output of 0.96 W cm -2 at 700 °C, while the power output for the cell with a conventionally sintered cathode is 0.33 W cm -2 .